2010
DOI: 10.1105/tpc.110.078543
|View full text |Cite
|
Sign up to set email alerts
|

Clustered Transcription Factor Genes Regulate Nicotine Biosynthesis in Tobacco  

Abstract: Tobacco (Nicotiana tabacum) synthesizes nicotine and related pyridine alkaloids in the root, and their synthesis increases upon herbivory on the leaf via a jasmonate-mediated signaling cascade. Regulatory NIC loci that positively regulate nicotine biosynthesis have been genetically identified, and their mutant alleles have been used to breed low-nicotine tobacco varieties. Here, we report that the NIC2 locus, originally called locus B, comprises clustered transcription factor genes of an ethylene response fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
371
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 224 publications
(397 citation statements)
references
References 66 publications
25
371
0
1
Order By: Relevance
“…These findings are also in agreement with those of Shoji et al (2010), who showed that gain-and loss-of-function of another clade 2-1 NIC2-locus ERF, i.e. ERF189, increased and decreased significantly the accumulation of nicotine in transgenic tobacco hairy roots, respectively.…”
Section: Orc1 Stimulates Nicotine Biosynthesis In Nicotiana Speciessupporting
confidence: 82%
See 3 more Smart Citations
“…These findings are also in agreement with those of Shoji et al (2010), who showed that gain-and loss-of-function of another clade 2-1 NIC2-locus ERF, i.e. ERF189, increased and decreased significantly the accumulation of nicotine in transgenic tobacco hairy roots, respectively.…”
Section: Orc1 Stimulates Nicotine Biosynthesis In Nicotiana Speciessupporting
confidence: 82%
“…These NIC2-locus ERF TFs are close homologues of the C. roseus ORCA3 and showed both functional redundancy and divergence in their capacity to regulate nicotine biosynthesis. Similar to the involvement of ORCA3 in TIA biosynthesis, NIC2-locus ERFs activate most of the known structural genes in the tobacco nicotine biosynthesis pathway and bind a GCC motif in the PMT promoter (Shoji et al, 2010). In agreement with these findings, we previously showed that two JA-inducible AP2/ERF TFs from tobacco, ORC1 and JAP1, positively regulate the PMT promoter in a protoplast-based transient expression assay (Goossens et al, 2003;De Sutter et al, 2005).…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…genes in each step (Shoji et al 2010). In our experiments, we chose to analyze the expression of the genes coding for PMT, A622, and CYP82E4 because of the availability of a known gene sequence in the public databases and also due to their key location in different branches of the pyridine alkaloids biosynthesis pathway in tobacco.…”
Section: Discussionmentioning
confidence: 99%